Porosity of sediment samples from MeBo core GeoB23213-1 recovered from west off Taiwan (South China Sea) - Thomas Pape; Janice Malnati; Gerhard Bohrmann (PANGAEA, 2022)
Sediment cores were collected from several sites west off Taiwan, South China Sea, with the sea floor drill rig MARUM-MeBo200 during cruise SO266 with R/V SONNE. In order to determine the fraction of the volume of voids over the total volume, sediment samples were taken from the sediment cores with cut-off syringes and transferred into preweighed plastic cups. The water content and porosity of the samples were calculated based on their wet weight and dry weight.